A comparative study of RIPASA and Alvarado score for the diagnosis of acute appendicitis - Suresh, Praveena; Janardhanan, Rajan; Paul, Deepak (International Surgery Journal, 2020)
Background: Acute appendicitis is a common problem and can be difficult to diagnose at time. There are many scoring systems to predict the diagnosis of acute appendicitis. The most commonly used scoring system is Alvarado scoring system but, it is far from perfect. In this study we compare Raja Isteri Pengiran Anak Saleha Appendicitis (RIPASA) scoring system to Alvarado scoring system in correctly diagnosing acute appendicitis. Methods: This prospective observational study was conducted in the department of general surgery, Sree Gokulam Medical College and Research Foundation. It comprised of 60 consecutive patients who were admitted with suspicion of appendicitis who had right iliac fossa pain. RIPASA and Alvarado scoring was done and compared to histopathology after surgery. Sensitivity, specificity and accuracy was calculated. Results: Majority of the patients were below 30 years of age majority were males 36 (60%). When Alvarado score predicted appendicitis in 31 (51.77%) and RIPASA in 54 (90%). When the RIPASA score was >7.5 the sensitivity was 100%, specificity 67% and accuracy was 95%. Conclusions: RIPASA scoring system is more accurate to diagnose acute appendicitis especially when RIPASA score is >7.5. literatures.